Analysis of use of Percutaneous Nephrostomy and Ureteral Stenting in Management of Ureteral Obstruction - Yasrab, Muhammad Nauman Iqbal, Qurat-Ul-Ain Khan, Hafiz Muhammad Asim Mushtaq, Syeda Samina Asad, Aftab Ahmed (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Urinary diversion is one of the ways to manage ureteral obstructions and is commonly performed in our daily practice when the underlying condition of ureteral obstruction cannot be eliminated in a short period. Ureteral obstructions can be a consequence of malignancies or benign diseases. Aims and objectives: The basic aim of the study is to analyze the use of percutaneous nephrostomy and ureteral stenting in management of ureteral obstruction. Methodology of the study: This cross sectional study was conducted at Department of Urology, Shaikh Zayid Hospital Lahore during October 2020 to Dec 2021. This study was done with the permission of ethical committee of hospital. There were 110 patients who selected for this study analysis. Enrollment criteria consisted of the need for unilateral or bilateral upper urinary tract diversion for at least 6 months. Either a PCN tube or an internal ureteral stent (e.g., double-J stent) was used for ureteral obstructions of various etiologies. Results: There were 110 patients with mean age 60 years in this study. There were 66 patients with ureteral stents and 44 (40%) with PCN tubes. A smaller elevation in serum creatinine was noted in the PCN group (0.21 vs. 0.78 mg/dL, p = 0.03). Nine of 86 (10.4%) double-J stents were converted to PCN tubes during the study period. Residual hydronephrosis after decompression was more common in the stent group than in the PCN group (65.2% vs. 27.2%, p = 0.01). Conclusion: It is concluded that Urinary diversion or decompression using PCN produced better preservation of renal function and lower incidences of complications in our study.